Fluid Bolus for Renal Colic: Current Practice. Issue 5 (September 2015) - Tarplin, Sarah; Larson, Benjamin; Byrne, Michael; Loftus, Christopher; Monga, Manoj
Abstract : Introduction: : Historically the administration of intravenous fluid boluses in patients with urolithiasis and acute renal colic has been a standardized practice in the emergency department as a part of a conservative approach. In theory, an intravenous fluid bolus may promote ureteral fluid flow. However, randomized, controlled trials have shown no benefit of fluid boluses in this setting. We assessed current fluid bolus practices in community and tertiary care emergency departments. Methods: : We analyzed all emergency department visits in the Cleveland Clinic health care network with an ICD‐9 diagnosis of 592.0 and computerized tomography of the abdomen/pelvis between December 7, 2010 and May 6, 2013. The incidence of intravenous fluid bolus administration was assessed, and patient demographics, serum laboratory values and urinalysis were collected. Cases with a blood urea nitrogen‐to‐creatinine ratio greater than 20 were considered hypovolemic and urine specific gravity values greater than 1.030 were considered suggestive of hypovolemia. Results: : Overall 60.2% (3, 037 of 5, 048) of patients with nephrolithiasis and computerized tomography received intravenous fluid boluses. The majority of patients who received a fluid bolus (79.12%) did not meet the criteria for volume depletion based on blood urea nitrogen‐to‐creatinine ratio or urine specific gravity. In addition, there was no statistically significant difference in the proportion of patients with a blood urea nitrogen‐to‐creatinine ratio greater than 20 among those who received fluid boluses (25.50%, 617 of 2, 420) and those who did not (25.45%, 408 of 1, 603; p=1.00). Conclusions: : The use of forced fluids continues to be a common practice in emergency departments and they are frequently administered despite normal blood urea nitrogen‐to‐creatinine ratios. Thus, it is likely that fluids are not administered due to hypovolemia but rather due to practice approaches rooted in historical dogma and the lack of guidelines on this topic.